1989
DOI: 10.1002/cjce.5450670308
|View full text |Cite
|
Sign up to set email alerts
|

Sequential statistical design strategy in a kinetic study of propylene oxidation

Abstract: A sequential design strategy was used to direct an experimental kinetic study of propylene oxidation over bismuth molybdate. Two statistical criteria were used to design experiments. The first is a joint criterion for the dual problem of model discrimination and parameter estimation which was proposed by Hill et al. (1968), but which to the best of our knowledge has not been tested in an experimental program. Using this joint criterion design, it was demonstrated that both the objectives of model discriminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…An initial-rate study of propylene oxidation was completed first (Tan et al, 1988), using a joint criterion design for model discrimination and parameter estimation (Tan et al, 1989). The results were combined with results from a previous initial-rate study of propylene oxidation on the same catalyst to develop a quantitative description of the reaction network for propylene oxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An initial-rate study of propylene oxidation was completed first (Tan et al, 1988), using a joint criterion design for model discrimination and parameter estimation (Tan et al, 1989). The results were combined with results from a previous initial-rate study of propylene oxidation on the same catalyst to develop a quantitative description of the reaction network for propylene oxidation.…”
mentioning
confidence: 99%
“…An initial-rate study of propylene oxidation was completed first (Tan et al, 1988), using a joint criterion design for model discrimination and parameter estimation (Tan et al, 1989). An initial-rate study of propylene oxidation was completed first (Tan et al, 1988), using a joint criterion design for model discrimination and parameter estimation (Tan et al, 1989).…”
mentioning
confidence: 99%
“…For each of the two sets of experiments in Figure 1, the parameter estimates are reported for the experimental and high error variances. All our estimates are obtained one run after discrimination is achieved and surprisingly have narrower confidence limits than those reported by Tan et al (1988Tan et al ( , 1989, Table 1. The parameter values we selected for simulation (bottom of Table 1) are contained in all the confidence intervals except one.…”
Section: Precise Parameter Estimationmentioning
confidence: 46%
“…However, their study showed that the guesses could range over many orders of magnitude in a wide variety of combinations. Yet, the probability found for the correct model was essentially unity with the absolute minimum number of runs needed for discrimination.In this study, the Initial-runs JDC was used to discriminate between the two main rival kinetic models for the oxidation of propylene (Tan et al, 1989). The criterion was used to design all runs, including the preliminary ones, that in the work done by Tan et al (1989) were not designed by this criterion.…”
mentioning
confidence: 99%
See 1 more Smart Citation